Rebuilding Broadway: Retail Vacancy on East Somerville's Main Street: Assessing Causes, Challenges, and Remedies. - Leonardo, Dominic.; Murthy, Srilekha.; Naughton, Lindsay.; Rubelmann, Adam.; Wilson, Erik. (Tufts Archival Research Center, 2021)
2021 M.A. in Urban and Environmental Policy and Planning Field Project. Client: East Somerville Main Streets.